Healthy men, sick women? A study on the life expectancy and health of the Portuguese population (Brazilian Journal of Health Research, 2019)
Introduction: Significant improvements in population health status, such as increased human longevity and new shaped realities are differently expressed in men and women. There is significant divergence between sexes when it comes to health and to the ability to survive: men are physically stronger and have fewer difficulties, but they record substantially higher mortality rates than women at all ages. Women live longer, but they live with worse health conditions. This is the health and survival paradox involving the male-female relationship. Objective: Identifying mortality patterns and health profiles, based on sex and age, in men and women at the age group 50+ years. Methods: Both, mortality data over time and a search based on the database of the National Health Survey (INS), 2005/06, were used in the research. Results: Portuguese elderly women have worse schooling level and greater risk of living in poverty due to lower income and social status; however, the overall population of older individuals in Portugal presents unfavorable social conditions. Women often have poorer health and more comorbidities, but they live longer than men. Evidences show that poorer health and unhealthy practices are associated with lower income and with undifferentiated work activity, but these factors are not directly associated with sex. Conclusion: Sex-related factors play an important role in explaining differences in health conditions experienced throughout life. These differences become clearer throughout the aging process both in men and women.